A Review: Synthesis and Medicinal Importance of Nicotinonitriles and Their Analogous. (21st May 2018) - Gouda, Moustafa A.; Hussein, Belal H. M.; Helal, Mohamed H.; Salem, Mohammed A.
Abstract : The biological, therapeutic, and medicinal properties of nicotinonitriles (cyanopyridines) and its analogues have prompted enormous research aimed at developing synthetic routes to these heterocyles. This review presents a systematic and comprehensive survey of the method of preparation, the chemical reactivity, and biological properties associated with this system. Abstract :